INCREASING OPERATION EFFECTIVITY OF METAL PRODUCTS LOADING POINTS BY THE RATIONAL USE OF BRIDGE CRANES - Turpak, S. M.; Vasylieva, L. O.; Padchenko, O. O.; Lebid, H. O. (Science and Transport Progress, 2019)
Purpose. Taking into account research and improvement of transport and storage processes for loading railway cars with bridge cranes the purpose of the study is the analysis of actual crane operation zones, development of simulation models of their functioning and determination of the most effective load technology. The real object of the study — the finished goods warehouse of a metallurgical enterprise — is formalized as a linear load point. Methodology. To analyse various options for the crane operation zones of the investigated object, the simulation modelling method was used. It was taken into account that each bridge crane can load railway cars, which are located in different zones of the loading track. Situations when the cranes are on the same crane ways during cargo operations and the service area of cars partially coincides were considered. Under such conditions, cranes can interfere with each other; it makes it difficult to carry out the transport-technological process of loading. Findings. A simulation model in which the service elements, which are the individual cargo packages, move along certain routes has been developed. Freight traffic volumes are set according to certain laws of random value distribution, taking into account the stochastic nature of real transport processes. A model of the linear loading point of railway cars with bridge cranes has been developed. It allows us to analyse the performance indicators of various options for assigning service areas to loading facilities. The analysis of such indicators as an average transporting time of service elements, a time percentage of cranes work and idle, time for separate movement operations of freight traffic volume is performed. Based on the developed model, a procedure has been developed to determine the most effective strategy for managing the loading point operation. The methodology, which has been tested on the example of a finished product warehouse of a metallurgical enterprise, and allows reducing the total costs in the process of rolled metal products loading has been developed. Originality. Theoretical research and improvement of the operation models of the metallurgical enterprise`s transport and storage complex due to the rational assignment of vehicle loading areas to the cranes. Practical value. The results obtained make it possible to increase the efficiency of the transport and storage complex by reducing the time spent by railway cars in the system with the rational use of loading resources.